2017
DOI: 10.18488/journal.1.2017.78.684.695
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Entrepreneurship Amidst Poverty and Unemployment: The Role of Nigerian Educational Policies

Abstract: Article History

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…In the current business context, managers need to accept and adopt the change to remain competitive because of the rapid evolution of technology and new regulations [54,55]. Xu, et al [56] indicated that managers need to adopt change because the world evolves with the increasing number of people, businesses, and regulations.…”
Section: Adaptation To Changementioning
confidence: 99%
“…In the current business context, managers need to accept and adopt the change to remain competitive because of the rapid evolution of technology and new regulations [54,55]. Xu, et al [56] indicated that managers need to adopt change because the world evolves with the increasing number of people, businesses, and regulations.…”
Section: Adaptation To Changementioning
confidence: 99%
“…In the current nonprofit organization's workplaces, managers need to understand and adopt change. The rapid evolution of technology and business regulations makes change irreversible to compete, increase customer service, or act efficiently in real-time [38]. Isal, et al [39] argued that using for instance technology innovation allows managers to assess controls, inventories, any other business activities at a low cost, and prevent fraud.…”
Section: Adaptation To Changementioning
confidence: 99%
“…In today's business context, managers need to promote changes in business practices to remain competitive because of the rapid evolution of technology and new business regulations [57,58]. Xu, et al [59] indicated that managers need to adopt change because the number of people in the world evolves every day, and this changes business statistics and predictions constantly.…”
Section: Adaptation To Changementioning
confidence: 99%